2015
DOI: 10.1007/s13361-015-1231-x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Mass Spectrometry-Based Peptidomic Approaches

Abstract: Abstract. Mass spectrometry-based peptidomic approaches are powerful techniques to detect and identify the peptide content of biological samples. The present study investigated the limitations of peptidomic approaches using trimethylammonium butyrate isotopic tags to quantify relative peptide levels and Mascot searches to identify peptides. Data were combined from previous studies on human cell lines or mouse tissues. The combined databases contain 2155 unique peptides ranging in mass from 444 to 8765 Da, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 60 publications
(118 reference statements)
0
44
0
Order By: Relevance
“…The amino acid composition of the peptides shows the most abundant amino acid is Ala (10.6%), with Lys, Val, Leu, Gly, Asp, and Glu also abundant ( Table 1 ). Cys is not detected in the peptidome, but this omission is likely to be an artifact of the extraction and/or labeling procedure [ 43 ]. Otherwise, the amino acid composition of the peptidome is generally similar to the amino acid composition of the intracellular and nuclear yeast proteome [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid composition of the peptides shows the most abundant amino acid is Ala (10.6%), with Lys, Val, Leu, Gly, Asp, and Glu also abundant ( Table 1 ). Cys is not detected in the peptidome, but this omission is likely to be an artifact of the extraction and/or labeling procedure [ 43 ]. Otherwise, the amino acid composition of the peptidome is generally similar to the amino acid composition of the intracellular and nuclear yeast proteome [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous analysis of intracellular mouse brain peptides found that close to one half of the peptides represented the N- or C-terminus of the protein [ 16 ]. In contrast, proteomic studies that digest proteins with trypsin prior to MS analysis detect mainly peptides that are internal fragments of the protein [ 43 ]. Similar to the previous report on intracellular mouse peptides, 43% of the human cell line peptides represent either the N-terminus (26%) or C-terminus (17%) of the proteins from which the peptides are derived ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…With caveats, such as the need to heat‐stabilize brain tissue prior to peptide extraction, the quantitative peptidomics technique used in this study is relatively unbiased and permits the detection of a large number of neuropeptides and other peptides in brain tissue (Fricker ). The proSAAS‐derived peptides are the most commonly detected peptides in peptidomic studies, consistent with the high abundance of these peptides in brain (Fricker ).…”
Section: Discussionmentioning
confidence: 99%
“…The mass spectrometer was tuned, calibrated and set with the same parameters as reported by Dei Più et al (2014). This approach suffers of several limitations especially related to the detection and identification of small peptides and any peptide containing free cysteine (Fricker, 2015). Small peptides (<500 Da) are often inefficiently ionized giving a low intensity m/z signal which hampered the selection of precursor for successive MS/MS fragmentation.…”
Section: Analysis Of the Peptidomic Profile Of Peptidic Fractions Of mentioning
confidence: 99%